167 Clinical Analysis on the Pharmaceutical Formulation of VIAGRA OD Film. (1st May 2022) - Shimoyama, H.; Sasaki, H.; Ogushi, Y.; Niikura, A.; Ota, T.; Ichimura, Y.; Hshimoto, Y.; Kurokawa, I.; Sugishita, H.; Tanifuji, S.; Yamagishi, M.; Imamura, Y.; et al.
ABSTRACT: : VIAGRA was first placed on the Japanese market in 1999. Since then, PDE5 inhibitors, such as VIAGRA, have been widely used as the first alternative therapeutic medication to treat erectile dysfunction (ED). A new form of VIAGRA called VIAGRA OD Film was launched in the Japanese market on October 21 st, 2016. OD film is taken orally without water and is fast dissolving. It is therefore expected to be easier to consume. Moreover, this medication is packaged in thin aluminum sheets to improve portability compared to the original tablets. For this study, we surveyed 25 patients to analyze the OD film formulation. These patients desired ED treatment and used the VIAGRA OD Film. All the participants answered our survey. They were aged between 21 and 79. Thirteen patients switched from the tablets to the OD film and 12 patients only used the OD film. The survey items included: 1) portability, 2) storage, 3) ease of consumption, 4) comfortableness, 5) level of self-consciousness with their partner, 6) thoughts on taking the film formulation, 7) comparison with the tablets, and 8) efficacy and adverse reaction. We observed that 61.5% of the patients who switched from tablets to film found that storage and portability were improved. Additionally, 61.5% of the patients who switched from tablets to film and 75.0% of the patients who were prescribed film only were able to comfortably swallow them. We also found that 69.2% who switched from tablets to film and 75.0% who were prescribed film only felt more at ease using it and 61.5% who switched from tablets to film and 66.7% who were prescribed film only felt more comfortable with the film. Finally, 28.0% of the individuals stated a negative opinion on the ease of consuming the OD film. The efficacy of the film was the same as the tablets. We identified two cases of adverse reactions with mild hot flashes and headache but no severe adverse reaction. This survey indicates that the ease of intake and portability was improved with OD film. Disclosure: Work supported by industry: no.